Genetic diversity of Ulva lactuca from the intertidal zone in Ulee Lheue beach Aceh, Indonesia - RAHMAH HAYATI; FAWWA RAHLY (Jurnal Natural, 2024)
Ulee Lheue Beach in Banda Aceh was developed for tourism. The macroalgae and seaweed species found in this area have been widespread but never exploited. Among these species is the green seaweed, Ulva lactuca, commonly known as sea lettuce. The physiological variations and genetic features of the seaweed can be attributed to the variations in the coastal environment. This study aims to describe the molecular identity of the genetic diversity of U. lactuca from the intertidal zone at Ulee Lheue Beach. The development of molecular biotechnology has enabled identification the gene expression through genomic DNA to PCR amplification. Genetic distance was determined using UPGMA. The results from 600-bp fragments were analyze the genetic diversity. A total of 15 (31%) expression identified as polymorphic (0.500). Heterozygosity (He) and allelic differential (Na) diversity were found of 1.500–3.000. The highest PIC was observed in the rbcL1, with a correlation between subpopulations of 0.459. PCR amplification using the degenerate primer rbcL1 produced fragments ranging from 300 to 460 bp, whereas the expression of UL2 was detected at 448 and 500 bp using the rbcL2 primer. The phylogenetic identify are shown two (2) clusters. The populations of UL1, UL3, and UL4 were found a close relationship. Furthermore, the UL1 and UL2 populations were further divided into distinct clusters but related to the main branch of UL3. Based on this research, the concern of U. lactuca species for industrial and biotechnology destinations, we can describe a suitable method for obtaining he genetic distances between species.